ОСОБЕННОСТИ ИНФЛЯЦИОННЫХ ПРОЦЕССОВ В КАЗАХСТАНЕ. (Journal of Economic Research & Business Administration, 2016)
The scientific article is devoted problems of interrelation of inflations and economic growth and measures on decrease in rate of depreciation of money because rates of inflation is one of the major macroeconomic indicators whom influences interest rates, rates of exchange, consumer and an investment demand, for many social aspects, including for cost and quality of life.